Wolbachia superinfections and the expression of cytoplasmic incompatibility. - Sinkins, S; Braig, H; O'Neill, S (1995)
Strains of Drosophila simulans from Riverside, California (DSR) and Hawaii (DSH) harbour distinct strains of the cytoplasmic incompatibility microorganism Wolbachia, resulting in the expression of bidirectional incompatibility when crossed. D. simulans lines carrying both of these (superinfected) Wolbachia strains were generated by the transfer of infected DSH cytoplasm into DSR embryos by microinjection. The superinfected flies were unidirectionally incompatible with both DSR and DSH individuals. As a result of this pattern, the superinfected state was observed to replace single infections in laboratory populations. The ability of the superinfection to spread was modulated by the production of singly infected offspring from superinfected mothers: strain segregation was observed under crowded larval rearing conditions. An inverse correlation between the penetrance of the cytoplasmic incompatibility phenotype and the degree of larval crowding was also observed. The findings have implications for the evolution of bidirectionally incompatible strains, and lead to the prediction that superinfections should be relatively common in field populations. Evidence for a natural superinfection in the mosquito Aedes albopictus is discussed. The results also have applied significance for the generation of insect lines capable of driving desirable genes into populations already infected with Wolbachia, thus allowing repeated opportunities for population replacement.